1998
DOI: 10.1016/s0002-9270(98)00404-3
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and gastroesophageal reflux disease: the bug may not be all bad

Abstract: Peptic ulcer disease and gastric cancer of the antrum and body have been declining in the 20th century. In contrast, a new group of diseases are increasingly rapidly in Western countries: gastroesophageal reflux disease, Barrett's esophagus, and adenocarcinoma of the distal esophagus. Recent studies suggest this phenomenon may be related to the simultaneous fall in the prevalence of Helicobacter pylori (H. pylori) colonization, especially by the virulent cagA + strains. H. pylori infection with the cagA+ strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 0 publications
1
50
0
2
Order By: Relevance
“…The PG-I/ PG-II ratio did not correlate with gastric acidity; this might be related to the fact that our study population included patients with antral (high acid) and pangastritis (reduced acid) both among H. pylori infected group, thus balancing the effect of each other. Secondly, presence of H. pylori itself increases the gastric pH probably due to inflammation of the stomach and buffering of acid because of ammonia [47,48]. However, among patients without H. pylori infection, higher PG-I/PG-II ratio correlated with gastric acidity.…”
Section: Discussionmentioning
confidence: 99%
“…The PG-I/ PG-II ratio did not correlate with gastric acidity; this might be related to the fact that our study population included patients with antral (high acid) and pangastritis (reduced acid) both among H. pylori infected group, thus balancing the effect of each other. Secondly, presence of H. pylori itself increases the gastric pH probably due to inflammation of the stomach and buffering of acid because of ammonia [47,48]. However, among patients without H. pylori infection, higher PG-I/PG-II ratio correlated with gastric acidity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that gastric atrophy induced by chronic H. pylori infection results in hypoacidity and in turn reduces the tendency for chronic gastresophageal reflux, Barrett's and esophageal carcinoma [4]. Absence of H. pylori would thus enhance the esophageal acid load for those who experienced gastresophageal reflux leading to more severe clinical disease, a higher incidence of Barrett's esophagus, and subsequently adenocarcinoma of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…This rise has been linked to the increasing prevalence of obesity, gastresophageal reflux, and Barrett's esophagus. It has also been suggested that the decline in the prevalence of Helicobacter pylori (H. pylori) and the consequent changes in gastric acid homeostasis resulting in a higher esophageal acid load may be contributory [1][2][3][4]. Indeed an inverse relationship has been suggested between H. pylori infection and the risk of esophageal adenocarcinoma [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This has not proven to be the case in the available US studies. At present, the higher dose of clarithromycin is recommended within the United States [4,48].…”
Section: Factors Influencing the Effectiveness Of Therapymentioning
confidence: 99%
“…The inflammatory and neurohumoral effects induced by H. pylori differ from individual to individual, likely related to host and bacterial strain heterogeneity. This heterogeneity may explain why some individuals develop antral predominant gastritis and duodenal ulcer while others develop body-predominant gastritis, intestinal metaplasia, and gastric malignancy [4]. In fact, recent studies suggest that there may be an inverse relationship between duodenal ulcer and gastric cancer [5].…”
Section: Introductionmentioning
confidence: 99%